A preliminary engineering geological study in the northern part of the Taplejung Window, far eastern Lesser Nepal Himalaya (Journal of Nepal Geological Society, 2004)
In the northern part of the Taplejung area, two tectonic units are recognised. These are the Higher Himalayan and Lesser Himalayan Sequences separated by the Main Central Thrust (MCT). The Lesser Himalayan Sequence is exposed in the Taplejung Window represented by Taplejung Formation, Mitlung Augen Gneiss, and Lingkhim Schist from the bottom to top. The main rock types in the Lesser Himalayan Sequence are phyllite, schist, metasandstone, quartzite and augen gneiss. Three Proterozoic granitic bodies are intruded into Taplejung Formation: Tamor River Granite, Amarpur Granite and Kabeli Khola Granite. The rocks of the Higher Himalaya on the hanging wall of the MCT are composed of kyanite-sillimanite bearing banded gneiss, orthogneiss, migmatite, quartzite.Three major landslides in the area, viz., Hangdewa, Hireba, and Paire lie along the valley slope sides of the Tamor River. Stream erosion and incision, presence of highly weathered rocks, surface and subsurface drainage are responsible in activating the landslides. Due to the presence of mainly weathered phyllites, favourable structural orientations and wet cultivation practice in the area have contributed to the development of these landslides.  The Hangdewa and Hireba landslides have endangered the villages in between them and ultimately the Suketar airport. The landslides are gradually destroying more and more areas of cultivated land and property and increased loss of human lives.Excessive anthropogenic interference in the form of development activities like unplanned urbanization, deforestation and unfavorable agricultural practices have greatly aggravated the situation. The intensity of damages amplifies during the late part of monsoon each year. The study suggests that further detailed surface and subsurface investigation of the landslides are needed to prevent further loss of lives and property.